(untitled) (Journal of the College of Basic Education, 2022)
The current research aims know the percentage of future thinking skills in the content of the sixth grade mathematics book for the academic year (2021-2022), the researcher used the descriptive analytical approach method, and the research sample consisted of a sixth-grade mathematics book approved in the academic year (2021-2022), A content analysis tool was prepared for this purpose according to future thinking skills, and its validity was verified by presenting it to a number of experts, The idea unit (explicit and implicit), and (Holisti) adaptive reasoning and using frequency and percentages, and the research concluded that future thinking skills were all available at low rates, Visualization skill (29.65%), problem solving skill (24.02%), prediction skill (23.45%), representation skill (22.88%), respectively, In light of this, a number of recommendations were presented, including reconsidering the planning and writing of mathematics books in order to be compatible with modern trends that call for the development of education in a way that develops future thinking skills for all learners and at various levels of study, It was suggested to conduct a comparative study of the future thinking skills available in the content of mathematics books for the secondary stage in Iraq and other countries